EFFECTIVE USE OF LAND AND RESOURCES IN KAZAKHSTAN THROUGH REDUCED ECOLOGICAL EFFECTS (International Journal of Innovative Technologies in Economy, 2018)
This study investigates Kazakhstan’s agriculture in two sections. First, it discusses its importance, practical usage and research methods. Second, its benefit to the country, where effective land use is considered. It focuses on the usage of land and resources efficiently and at the same time to eliminate its negative impact on environment. It provides research based solutions for the issue. It has also supplemented with Kazakhstan’s agricultural reforms and President N. Nazarbayev’s messages to his country.The study was written in compliance with research requirements and has its importance.